Bilateral Morning Glory Anomaly With Optic Nerve Multiple Cysts. Issue 2 (June 2021) - Zhu, Xuemei; Wang, Yi; Liang, Jianhong
Abstract : Abstract: We herein describe a pediatric case of bilateral morning glory anomaly whose retrobulbar cysts and renal disease were underdiagnosed, and finally, he was diagnosed with renal coloboma syndrome. We recommend patients with colobomatous optic nerve malformations undergo a complete workup to avoid missed diagnosis, which includes (i) general physical examination looking for heart defects, genitourinary, auricular, and midline facial defects among other abnormalities; (ii) simple nephrologic investigations such as routine urine test and/or renal ultrasound to check for renal hypoplasia; and (iii) neuroimaging check for cerebrovascular anomalies and midline cranial defects. Genetic testing can be a useful tool to guide the workup.